2020
DOI: 10.1101/2020.02.27.967034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage-Antibiotic Synergy is Driven by a Unique Combination of Antibacterial Mechanism of Action and Stoichiometry

Abstract: The continued rise in antibiotic resistance is precipitating a medical crisis. Bacteriophage (phage) has been hailed as one possible therapeutic option to augment the efficacy of antibiotics.However, only a handful of studies have addressed the synergistic relationship between phage and antibiotics. Here, we report a comprehensive analysis of phage-antibiotic interaction that evaluates synergism, additivism, and antagonism for all classes of antibiotics across clinically achievable stoichiometries. We combi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
13
1
Order By: Relevance
“…Previous studies revealed synergistic effects by combining phage with an antibiotic for which the bacteria strain was resistant (Liu et al, 2020). In our study, however, the use of Sb-1 in combination with rifampin against biofilms of RRSA strains, as well as Sb-1/fosfomycin and Sb-1/gentamicin combinations against MRSA3 and MRSA ATCC 43300, respectively, did not reveal an improved anti-biofilm effect.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous studies revealed synergistic effects by combining phage with an antibiotic for which the bacteria strain was resistant (Liu et al, 2020). In our study, however, the use of Sb-1 in combination with rifampin against biofilms of RRSA strains, as well as Sb-1/fosfomycin and Sb-1/gentamicin combinations against MRSA3 and MRSA ATCC 43300, respectively, did not reveal an improved anti-biofilm effect.…”
Section: Discussioncontrasting
confidence: 86%
“…In combination therapies, two or more agents possessing different mechanisms of action can enhance each other’s activities 78–80 , broaden activity spectra 78,81–83 , reduce the potential for resistance evolution 84–91 , or improve penetration into biofilms 92 . One common aspect of phage therapy treatments is combining phages with antibiotics 38,92–102 . Here we have assessed the potential of different concentrations of two different classes of antibiotics, colistin and ciprofloxacin, to interfere with infection activities of P. aeruginosa phage PEV2 and other tested phages at bacterial growth-inhibiting antibiotic concentrations (≥MIC).…”
Section: Discussionmentioning
confidence: 99%
“…To test synergy across antibiotics, the standard is a checkerboard assay (Martinez-Irujo et al, 1996), also referred to as synograph (Liu et al, 2020). This previously revealed tPAS reduced the effective ciprofloxacin MIC up to 32-fold, despite the poor effectiveness of phage alone condition (Al-Anany et al, 2021).…”
Section: Generalizability Of Tpas Across Different Quinolonesmentioning
confidence: 99%
“…PAS appears to be broadly applicable, spanning phages across the myoviridae (Chan et al, 2016;Comeau et al, 2007;Jansen et al, 2018;Kebriaei et al, 2020;Kirby, 2012;Liu et al, 2021;Malik et al, 2021;Ryan et al, 2012;Simon et al, 2021;Styles et al, 2020;Wang et al, 2020) siphoviridae (Knezevic et al, 2013;Li et al, 2021), and podoviridae families (Manohar et al, 2022;Save et al, 2022;Styles et al, 2020;Torres-Barceló et al, 2014Verma et al, 2009). In addition to phages, PAS has been demonstrated in many hosts: Klebsiella pneumoniae (Bedi et al, 2009;Pacios et al, 2021;, Pseudomonas aeruginosa (Chan et al, 2016;Chaudhry et al, 2017;Coulter et al, 2014;Duplessis et al, 2021;Engeman et al, 2021;Hagens et al, 2006;Oechslin et al, 2017), Actinobacter baumannii (Styles et al, 2020), Staphylococcus aureus (Chhibber et al, 2013;Dickey et al, 2019;Iqbal et al, 2020;Kaur and Chhibber, 2021;Kebriaei et al, 2020;Van Nieuwenhuyse et al, 2021;Yilmaz et al, 2013) and E. coli (Kim et al, 2021;Liu et al, 2020;Moradpour et al, 2020). PAS has also been demonstrated across antibiotics of multiple classes inclu...…”
Section: Introductionmentioning
confidence: 99%